Effects of a family-focused intervention model to promote the development of children’s oral language - Domeniconi, Camila; Gracia, Marta (Revista de Investigación en Logopedia, 2018)
The family-focused model interventions, as a way towards the family-centered intervention practices, takes advantage of the natural situations of daily routines to promote the development of children. The objective of the study was to implement and evaluate the effectiveness of an intervention focused on four families to achieve progress in the communication skills of their five-year-old children, measured through standardized language tests, and analysis of communicative activities with the children, parents and with the researcher. Families participated in five meetings where useful strategies to help children to achieve new communication challenges were discussed. The analysis of the data highlights that all children have improved their communication skills, in all assessments. They also reflect once again the importance of communicative interaction between adults and children, and the potential of a family-focused intervention model to promote advances in the communicative development of children.